Education: The Role Of Multimedia - Ling, Yeap Pau (2004)
The main focus of this study is to evaluate students' and lecturers' opinion towards the role of multimedia in enhancing education. It looks into the benefits of multimedia, the role of multimedia and the barrier in technology implementation and to obtain data, different research methods will be used.